Surface wave control in plasma-metal structures with perpendicular magnetic field - Akimov, Yu.A.; Azarenkov, N.A.; Olefir, V.P. (Вопросы атомной науки и техники, 2005)
The nonlinear interaction of high-frequency potential surface waves at a dense magnetized plasma-metal interface with a low-frequency plasma density modulation is considered in the point of view to control the surface waves. The influence of an external steady magnetic field directed perpendicularly to the interface and plasma parameters on temporal dynamics of the waves is studied. Розглянуто нелінійну взаємодію високочастотних поверхневих хвиль, що розповсюджуються вздовж межі густої магнітоактивної плазми з металом, із низькочастотними збуреннями густини плазми з точки зору контро лю за поверхневими хвилями. Вивчено вплив зовнішнього магнітного поля, перпендикулярного до межі розподілу, та параметрів плазми на часову динаміку хвиль. Рассмотрена возможность использования нелинейного взаимодействия высокочастотных поверхностных волн, распространяющихся на границе “плотная магнитоактивная плазма-металл”, c низкочастотными возмущениями плотности плазмы для управления поверхностными волнами. Исследовано влияние постоянного магнитного поля, перпендикулярного границе, и параметров плазмы на временную динамику волн.